2021
DOI: 10.3892/or.2021.8087
|View full text |Cite
|
Sign up to set email alerts
|

ND‑09 inhibits chronic myeloid leukemia K562 cell growth by regulating BCR‑ABL signaling

Abstract: Chronic myeloid leukemia (CML) accounts for approximately 15% of new adult leukemia cases. The fusion gene BCR-ABL is an important biological basis and target for CML. In the present study, a novel compound, ND-09, was developed and its inhibitory effect and mechanism of action on CML growth were evaluated using RT-PCR and western blot analysis. The results showed that ND-09 demonstrated a high level of inhibitory action toward CML cells overexpressing BCR-ABL and induced K562 cell apoptosis through the mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Moreover, TQ inhibited the phosphorylation of PI3K and Akt in oral squamous cell carcinoma (KB) cells [38]. Another study has demonstrated that the PTEN protein level was increased, and the PI3K protein level and the phosphorylation of its downstream molecules; Akt and mTOR, were decreased in K562 cells after treatment with ND-09 inhibitory compound [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TQ inhibited the phosphorylation of PI3K and Akt in oral squamous cell carcinoma (KB) cells [38]. Another study has demonstrated that the PTEN protein level was increased, and the PI3K protein level and the phosphorylation of its downstream molecules; Akt and mTOR, were decreased in K562 cells after treatment with ND-09 inhibitory compound [39].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid leukemia is a type of hematopoietic stem cell malignant tumor with the characteristics of differentiation disorder and uncontrolled proliferation (1,2). At present, the treatment of leukemia is mainly based on the combination of chemotherapy and targeted therapy, but there are obvious side effects and a high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid leukemia is a type of hematopoietic stem cell malignant tumor, with differentiation disorder, uncontrolled proliferation, or the inability of terminal differentiation of primitive cells to retain malignant proliferation ability and accounting for ~15% of new cases of adult leukemia (1,2). It has been confirmed that the occurrence of myeloid leukemia is associated with certain gene mutations, abnormal gene expression, epigenetic disorders or abnormal expression of non-coding RNA (3)(4)(5)(6).…”
Section: Mir-let-7c-3p Targeting On Egr-1 Contributes To the Committe...mentioning
confidence: 99%